CRISPR-Cas9-mediated editing of ZmPL1 gene improves tolerance to drought stress in maize - Chunlai Wang; Yangyang Zhou; Yimeng Wang; Peng Jiao; Siyan Liu; Shuyang Guan; Yiyong Ma (GM Crops & Food)
Maize (Zea mays L.) is a widely grown food crop around the world. Drought stress seriously affects the growth and development process of plants and causes serious damage to maize yield. In the early stage, our research group conducted transcriptome sequencing analysis on the drought-resistant maize inbred line H8186 and screened out a gene with significantly down-regulated expression, Phylloplanin-like (ZmPL1). The ZmPL1 gee expression pattern was analyzed under various abiotic stresses, and the results showed that this gene was greatly affected by drought stress. Subcellular localization analysis showed that the protein was localized on the cell membrane. In order to verify the role of ZmPL1 in drought stress, we overexpressed ZmPL1 in yeast and found that the expression of ZmPL1 could significantly increase the drought sensitivity of yeast. Next, ZmPL1 transgenic plants were obtained by infecting maize callus using Agrobacterium-mediated method. Under drought stress, compared with overexpression lines, gene-edited lines had higher germination rate and seedling survival rate, lower accumulation of MDA, relative conductivity and ROS, higher antioxidant enzyme activity, and the expression levels of stress-related genes and ROS scavenging-related genes were significantly increased. Exogenous application of ABA to each lines under drought stress attenuated the damage caused by drought stress on ZmPL overexpressing plants. In summary, ZmPL1 negatively regulates drought tolerance in maize.